ANALISIS PENGARUH SOSIAL MEDIA MARKETING TERHADAP KEPUTUSAN PEMBALIAN DI TOKO ARUMY FASHION STORE - Fasihul Lisan (Lembaga Penerbitan, Penelitian, dan Pengabdian kepada Masyarakat (LP3M) of Institut Badri Mashduqi Probolinggo Jawa timur Indonesia, 2022)
Nowadays, the development of information technology continues to increase. The positive impact of the continued development of information technology is the change in the marketing and promotion system in the business world, such as that of the Arumy Fashion Store which takes advantage of the opportunities for the development of digital technology by marketing its products through Social Media Marketing. On this basis, the purpose of writing this article is to find out whether Social Media Marketing, which is part of digital marketing, has an influence on product purchasing decisions at the Arumy Fashion Store. This study uses a quantitative descriptive research method with a total sample of 50 people. The number used as many as 48 people with sampling using random sampling technique. Collecting data through observation and questionnaires. The data analysis technique was carried out using simple linear regression analysis with SPSS software. The results showed that Social Media Marketing variables had an effect on purchasing decisions of 4,681 with a significance level of 0.000. While the magnitude of the influence of social media marketing on purchasing decisions is 57%. Then the remaining 43% is influenced by other variables not examined in this study.